Fundamentals of castory judgments on third party property and its implications against the pretensions of the claiming party - Salas Ponce, Lincoln (2020)
The problem lies in the fact that many times the third party does not obtain a sentence favorable to his claims, and even in cassary headquarters his right is rarely recognized. Although the third party accredits ownership of the property with a public or private document, other procedural legal circumstances prevent its right to be legally recognized. Precisely, it is the random judgments that provide us with the main foundations by which, the third party often fails to achieve his claim. In the present case, the random judgments corresponding to third-party proceedings of the years 2015-2016 have allowed us to fully understand the fundamentals that directly affect the judgment ruling; Likewise, it is possible to know the main aspects that occur in the judicial debate due to the prevalence of real law (property) over personal law (credit) even though the latter may be duly registered. Descriptive, correlational and explanatory research. The investigation has been carried out in a population of civil lawyers of the Tacna jurisdiction. Likewise, the documentary analysis represented by the judgments has been taken into account. The measuring instruments have been the questionnaires and the document analysis guide. It is concluded that the main grounds of the judgments analyzed on property third parties are related to the registration, the prevalence of the real property right over personal law and requirements for the appeal of cassation, denoting a regular favor to the plaintiffs.